Organization of the educational process of future specialists in graphic design using digital technologies - Olena Yefimenko (Scientific notes of the pedagogical department, 2023)
Today we live in the era of global digitalization of society. The rapid development of technologies and digitalization captures an ever-increasing spectrum of human activity, including educational and creative areas. Digitazation is rethinking approaches to the organization of the educational process, creative and project activities at the global level. Digital technologies should be understood as one of the tools in design activity in contemporary art, as well as an area for creaƟng immaterial virtual products.The purpose of the article is to highlight the impact of digital technologies on the organizaƟon of the educational process of graphic design specialists.Materials and methods. To achieve the research goal, a set of theoreƟcal methods was used: analysis and generalizaƟon of scienƟfic and methodical sources for theoretical substantiation of research problems, modeling, and synthesis of the obtained data.Research results. The main goal of design educaƟon is the formaƟon of a qualified specialist, a person capable  of  mastering  cultural  experience  and  modern  technologies,  including  digital  ones.  Design  is  a special type of activity in which innovative methods of project soluƟons and modern digital technologies are  widely  used  and  developed. Thus,  the  level  of  technological  development  and  digitalization  today  is more than ever stimulating the development and promotion of design education.Digitazation  promotes  the  introducƟon  of  webinars  and  video  conferences  into  the  educational process,  it  has  changed  the  form  and  type  of  organization,  as  well  as  the  availability  of  educational materials. Interactive media resources and digital technologies are increasingly used in modern design education.As  with  any  evolving  system,  digitazation  has  a  number  of  disadvantages  and  advantages.  On  the one  hand,  the  development  of  digitalization  gives  designers  an  unlimited  field  for  creativity  and  work. On the other hand, a number of problems and diﬃculties appear. For example, changes in the form of organization of work with the audience, including features and diﬀerences of physical objects and their digital copies, copyright, etc.